Promoting access to, and success in postgraduate education in South Africa: A synthesis of emerging issues - Saidi, A. (South African Journal of Higher Education, 2024)
This article evinces that policies and plans at the national level in South Africa recognise the importance of postgraduate education within the broader national education and training system, and that they place particular emphasis on promoting access to, and success in postgraduate education as one of the priorities on the country’s development agenda. It identifies and discusses ten issues that have a bearing on the national policies, plans, programmes and initiatives aimed at promoting access to, and success in postgraduate education. These issues emerge from the analysis, triangulation, and interpretation of sets of information and data obtained from multiple projects focusing on postgraduate education, that the Council on Higher Education has implemented since 2018. They are therefore referred to as “emerging issues”. They include the relatively small size of the postgraduate component of higher education, the pyramidal structure of the distribution of students across the different levels of postgraduate education, and the offsetting of the increase in the numbers of graduates produced at all levels of postgraduate education, by a corresponding increase in the numbers of students taking longer to complete their studies than the periods stipulated by the institutions, and by relatively high dropout rates. Other issues are about transformation, student funding, inadequate supervisory capacity, under-preparedness of students, and lack of adequate support services for postgraduate students. The article sets the scene for, and context of the other articles contained in this special issue of the South African Journal of Higher Education, and prepares the readers to understand and appreciate the contents of those articles.